Evolution of secretin family GPCR members in the metazoa - Cardoso, João CR (2006)
Background: Comparative approaches using protostome and deuterostome data have greatly contributed to understanding gene function and organismal complexity. The family 2 G-protein coupled receptors (GPCRs) are one of the largest and best studied hormone and neuropeptide receptor families. They are suggested to have arisen from a single ancestral gene via duplication events. Despite the recent identification of receptor members in protostome and early deuterostome genomes, relatively little is known about their function or origin during metazoan divergence. In this study a comprehensive description of family 2 GPCR evolution is given based on in silico and expression analyses of the invertebrate receptor genes. Results: Family 2 GPCR members were identified in the invertebrate genomes of the nematodes C. elegans and C. briggsae, the arthropods D. melanogaster and A. gambiae (mosquito) and in the tunicate C. intestinalis. This suggests that they are of ancient origin and have evolved through gene/ genome duplication events. Sequence comparisons and phylogenetic analyses have demonstrated that the immediate gene environment, with regard to gene content, is conserved between the protostome and deuterostome receptor genomic regions. Also that the protostome genes are more like the deuterostome Corticotrophin Releasing Factor (CRF) and Calcitonin/Calcitonin Gene-Related Peptide (CAL/CGRP) receptors members than the other family 2 GPCR members. The evolution of family 2 GPCRs in deuterostomes is characterised by acquisition of new family members, with SCT (Secretin) receptors only present in tetrapods. Gene structure is characterised by an increase in intron number with organismal complexity with the exception of the vertebrate CAL/CGRP receptors. Conclusion: The family 2 GPCR members provide a good example of gene duplication events occurring in tandem with increasing organismal complexity during metazoan evolution. The putative ancestral receptors are proposed to be more like the deuterostome CAL/CGRP and CRF receptors and this may be associated with their fundamental role in calcium regulation and the stress response, both of which are essential for survival.